Odontoblast-like Cytodifferentiation of Dental Stem Cells: A Review - Babaki, Danial; Matin, Maryam M (Iranian Endodontic Journal, 2020)
Dental problems are common in human populations. Traditional treatments are focused on managing caries, soft tissue impairments, functional defects, poor aesthetics, digestive disorders and alveolar bone resorption. During the last two decades, basic and clinical researches on adult stem cells have established a potential therapeutic concept in tissue regeneration. Among major cells responsible for tooth development, odontoblasts play a key role in the formation of organic and inorganic constituents of dental tissue. A premier stride in the development of novel stem cell-based strategies for the treatment of reversible and irreversible pulpitis is odontoblast regeneration. Among different candidate cell sources for odontoblastic regeneration, use of dental adult stem cells is a preferred option because of their great ability to differentiate into odontoblasts and also their minimally invasive isolation procedure. This review emphasizes on articles that report successful odontoblast-like differentiation of dental mesenchymal stem cells which in turn provide a background for dentin-pulp complex cell therapies, using genetic or chemical manipulation. The series of experiments both in vitro and in vivo asserted that dental mesenchymal stem cells can efficiently differentiate into functional odontoblast-like cells. However, the review shows there are drawbacks in present methods. Future research should focus on optimizing protocols on odontoblast differentiation of dental stem cells by simultaneously introducing different genes with mutual synergy, combined with chemical or recombinant protein introduction. Keywords: Dental Mesenchymal Stem Cells; Differentiation; Odontoblast